Mitigation of Leakage and Stationary Clutters in Short-Range FMCW Radar With Hybrid Analog and Digital Compensation Technique - Liu, Jingtao; Lu, Jingyun; Li, Yuchen; Gu, Changzhan; Mao, Junfa (IEEE transactions on microwave theory and techniques, 2022)
In short-range sensing, the frequency-modulated continuous-wave (FMCW) radar is subject to the leakage between the transmitter (Tx) and the receiver (Rx) and the stationary clutter reflections, which are difficult to deal with due to the proximity to the target. The proximity ghost image may not only interfere with the target but also pose limitations on the radar performance, such as the degradation of the signal-to-noise ratio (SNR). This article proposes a novel hybrid analog and digital compensation techniques, which mitigates the leakage and the stationary clutters by compensating with the prestored anti-interference signals in both analog and digital domains at the intermediate-frequency (IF) stage. A novel modulation signal-based synchronization (MBS) technique is developed to align the real-time IF signal with the anti-interference signal during the compensation process. By significantly suppressing both the Tx-Rx leakage and the stationary clutters, the proposed technique greatly improves the signal-to-interference ratio (SIR) of the IF beat signals and makes possible the detection of targets with weak reflections. Moreover, the analog compensation enables the full use of the dynamic range of the analog-to-digital converter (ADC), which will reduce the impact of quantization noise and, thus, improve the SNR. Experiments have been carried out to validate the performance of the proposed technique in leakage compensation, weak target detection, stationary clutter compensation, and gesture sensing. The experimental results show that the SIR and the SNR have been improved by around 38 and 10 dB, respectively.